Biomechanical study of the suture-affected area of the meniscal horn in the context of root detachment repairs. - Peña Trabalón, Alejandro (UMA Editorial, 2025)
This thesis focuses on the comprehensive characterization of the mechanical properties of sutured meniscal horn tissue in the area affected by the suture. The first aim is to develop a robust methodology to assess the mechanical response of sutured meniscal horns under circumferential tensile loads. Tissue-level properties, such as the stress-strain curve and stress needed for cut-out initiation, as well as specimen-level properties, such as the force needed to initiate tearing, are measured. Porcine models validates the approach, which is then applied to human menisci to analyze how age impacts mechanical properties across three groups: young (≤55 years), middle-aged (56–75 years), and older (>75 years). The study aims to determine if meniscal root repair can be beneficial for older patients, as recent clinical recommendations suggest. Results show that, despite reduced cut-out resistance in older meniscal tissue, a compensatory increase in horn thickness provides comparable overall resistance to younger samples. A comparison of mechanical properties of older human and porcine models versus younger human menisci assesses the suitability of these models as surrogates for studying younger tissue in vitro. Although commonly used in research, neither older human nor porcine models consistently replicate younger meniscus properties; however, each can serve specific study needs. The second objective quantifies axial compressive properties near the suture hole using unconfined indentation tests under pure axial and combined loading compression. Findings show elasticity-related parameters more than double under circumferential traction, though stress relaxation percentages remain unaffected. A finite element model of a sutured meniscal horn is also developed, integrating experimentally obtained properties, to study the improvement in computational predictions, revealing that the tissue's compressive behavior around the suture hole is more accurately predicted when using
Keywords: Menisco - Cirugía - Tesis doctorales; Biomecánica